Effect of Parasitic Element on 408 MHz Antenna for Radio Astronomy Application. (10th April 2014) - Anwar, Radial; Islam, Mohammad Tariqul; Misran, Norbahiah; Gopir, Geri; Yatim, Baharudin; Asillam, Mhd Fairos
Abstract : Antenna is one of the important subsystem components in a radio telescope system. In this paper, analysis on the effect of parasitic element on 408 MHz antenna in a radio telescope system is presented. Higher gain up to 10.24 dBi with reduction on beamwidth size has been achieved by optimizing the position of parasitic element relative to the driven element. The proposed antenna is suitable to be utilized in a transient radio telescope array.